PENGARUH FCF DAN KEBIJAKAN DIVIDEN PADA PEMBIAYAAN DAN UTANG PERUSAHAAN - Kusuma Wijaya; Siti Mujanah; Abdul Halik (Majalah Ekonomi, 2026)
The goal of this study is to look at how dividend policy and free cash flow affect the debt and financing policies of industrial companies. This study takes a quantitative approach by looking at financial statements from industrial companies listed on the Indonesia Stock Exchange from 2021 to 2025. This sampling method used purposive sampling, which means choosing samples based on certain criteria (in this case, the study's goals). It included 13 companies for a five-year observation period. We used statistical software to figure out descriptive statistics, frequency counts, and percentage scores from the data we collected. We also used classical assumption tests, multiple linear regression analysis, and hypothesis tests. The study used purposive sampling to choose a sample of 65 financial reports. We used SPSS version 24's analysis tools to work with the data we got. This study used classical assumption tests and normality tests to do hypothesis testing with multiple linear regression methods. The results show that dividend policy has a big effect on how companies handle their finances and debts. Free cash flow also shows that the industrial sector has a big effect on how companies get money and how they handle debt.